PENGARUH PENGHINDARAN PAJAK TERHADAP CASH HOLDING PERUSAHAAN DENGAN LEVERAGE DAN RETURN ON ASSET (ROA) SEBAGAI VARIABEL MODERASI - Dessy Natalia Tambunan; Aditya Septiani (Diponegoro Journal of Accounting, 2017)
This  study  aims  to  obtain  empirical  evidence  and  analyze  the effect  of  tax avoidance on the company's cash holding, as well as the effect of leverage and ROA can moderate the tax avoidance of the cash holding companies.The population in this study is a manufacturing company listed on the Indonesia Stock Exchange Period 2013-2015. The samples selected for use in this study are 223 companie sample that meet the criteria of the sample. The data of this research are analyzed  by using  descriptive analysis,  classical  assumption  test,  hypothesis  test  with simple linear regression test and multiple linear regression test.The result of this research analysis shows that tax avoidance has a significant negative effect to the company's cash holding, leverage has a significant negative effect in moderating the effect of tax avoidance on the company's cash holding, and Return On Assets (ROA) has a significant negative effect in moderating the effect of tax avoidance on cash holding company.